2022
DOI: 10.1186/s12866-022-02678-9
|View full text |Cite
|
Sign up to set email alerts
|

Comparative genomics and genomic diversity of Pseudomonas syringae clade 2b-a in Australia

Abstract: Background A zucchini disease outbreak with unusual symptoms associated with Pseudomonas syringae clade 2b was identified in Bundaberg, Australia during autumn 2016. To investigate the genetic diversity of the 11 Australian isolates obtained from the outbreak, the genomes were compared to the publicly available P. syringae strains in phylogroup 2. Results Average nucleotide identity refined the P. syringae clade 2b-a into four clusters (Cluster A, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 51 publications
0
3
0
Order By: Relevance
“…The test based on sylC was multiplexed with qPCR tests targeting avrRpt2 and hopZ5. The gene encoding the T3E AvrRpt2 is present in all VCZ strains that have a narrow host range on cucurbits (Lacault et al 2020;Djitro et al 2022a) but also in the pathovar tomato (Innes et al 1993) and was found in some strains of pathovars maculicola, spinaceae and tagetis that were not known to have it. Indeed, avrRpt2 was not included in the large analysis of the distribution of virulence encoding genes including 53 T3Es in Pseudomonas syringae made by Sarkar et al (2006).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The test based on sylC was multiplexed with qPCR tests targeting avrRpt2 and hopZ5. The gene encoding the T3E AvrRpt2 is present in all VCZ strains that have a narrow host range on cucurbits (Lacault et al 2020;Djitro et al 2022a) but also in the pathovar tomato (Innes et al 1993) and was found in some strains of pathovars maculicola, spinaceae and tagetis that were not known to have it. Indeed, avrRpt2 was not included in the large analysis of the distribution of virulence encoding genes including 53 T3Es in Pseudomonas syringae made by Sarkar et al (2006).…”
Section: Discussionmentioning
confidence: 99%
“…Individually the three PCR tests targeting genes encoding the pathogenicity factors SylC, AvrRpt2 and HopZ5 were not specific for VCZ strains (Supplementary Table 2). However, VCZ strains from main clusters are characterized by the simultaneous presence of sylC and either avrRpt2 or hopZ5 (Figure 2 and Table 1), as avrRpt2 characterizes 2ba strains that have a narrow host range on cucurbits whereas hopZ5 is present in strains with a wider host range (Lacault et al 2020;Djitro et al 2022a). Clade-2b* and -2d strains were also isolated from zucchini seeds and gave a positive signal with 4Ba test (targeting sylC) justifying the need to include their corresponding qPCR tests in the multiplex.…”
Section: Development Of a Multiplex Qpcr Test To Identify Vcz Strainsmentioning
confidence: 99%
See 1 more Smart Citation